Sintilimab-induced myocarditis suspected in a patient with esophageal cancer and followed septic shock: case report and literature review - Zhou, Qihao; Qin, Zhiquan; Wu, Guoqing; Yan, Peiyuan; Wang, Qunjiang; Qu, Jing; Jiang, Jiahong (Frontiers in Oncology, 2024)
BackgroundImmune checkpoint inhibitors (ICIs) have become a prevalent tool in anti-tumor therapy in recent years. They may cause immune-related adverse events (irAEs) including potentially life-threatening cardiovascular toxicities such as myocarditis.Case presentationIn this report, we describe a 69-year-old man with recurrent esophageal cancer who developed myocarditis after receiving three cycles of sintilimab combined with nab-paclitaxel. Despite a rising cardiac troponin I (cTnI), he initially reported no discomfort. He was later suspected of having with sintilimab-induced myocarditis. Although treatment with methylprednisolone reduced his cTnI levels, he still experienced significant discomfort. Moreover, he developed pneumonia and septic shock.ConclusionIn our literature search to identify all reported cases of sintilimab-associated adverse events involving myocarditis, we found 14 patients, including those with esophageal cancer, thymoma, lung cancer, gastric cancer, hepatobiliary carcinoma, and chordoma. The primary treatment for ICI-induced cardiotoxicity is methylprednisolone. However, the long-term or high-dose use of steroids can also induce side effects, which have not been the focus of these case reports. This is the first reported case of asymptomatic immune-mediated myocarditis occurring during the treatment of esophageal cancer with sintilimab. It is also the first to address the side effects of methylprednisolone used in the treatment of sintilimab-related myocarditis. To facilitate an early diagnosis, regular monitoring is required during sintilimab treatment. We should also focus on the prevention and management of adverse effects related to steroid use.